HUBUNGAN ANTARA BEBERAPA PARAMETER ANEMIA DAN LAJU FILTRASI GLOMERULUS PADA PENYAKIT GINJAL KRONIK PRADIALISIS - Paramita Ayu, Nyoman; Suega, Ketut; Raka Widiana, Gede (journal of internal medicine, 2010)
Anemia is one of chronic kidney disease (CKD) complication and it affects many organs including cardiovascular. Earlydetection and evaluation are important to prevent more serious complications. There is scarce data with regard about correlationbetween anemia and glomerulus ltration rate (GFR) in pradialysis CKD.Aim of this study is to determine correlation between anemia parameters and GFR, also prevalence of anemia in pradialysisCKD in Sanglah Hospital, Denpasar-Bali. An analytical cross sectional study was carried out in Sanglah Hospital. Samples wereselected through simple random sampling.Eighty samples (58 males and 22 females, aged 54 ± 10 years) were included. Prevalence of anemia, serum iron belowthan 50 ug/dl, transferrin saturation below than 20% and erythropoietin below than 5 mIU/ml was 41.3%, 25%, 20%, and 25%respectively. Using Pearson?s analysis, there were signicant correlation between haemoglobin (r = 0.76, p = 0.00) and serumiron (r = 0.29, p = 0.01) with LFG. Using linier regression entering those variables into model, it found formula haemoglobin= 7.63 + 0.13GFR (R-square = 0.58, p = 0.00) and serum iron = 54.71 + 0.48GFR (R-square = 0.08, p = 0.01). There wassignicant correlation between haemoglobin and serum iron with LFG. Forty one percent pradialysis CKD patients had anemiacomplication.